Research advances in the immune microenvironment in alopecia areata - Rui QIAO; Yiqun JIANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
The pathogenesis of alopecia areata, a common autoimmune non-scarring alopecia, remains unclear. Current studies have shown that the loss of immune privilege of hair follicles due to the up-regulation of MHC molecules and the decrease in immunosuppressive molecules leads to the exposure of self-antigens in the affected area. This triggers the infiltration of immune cells (such as CD8+ T cells, NK cells, plasmacytoma dendritic cells, and mast cells) around the hair bulb. Various immune cells and related cytokines participate in the pathogenesis and development of this disease through diverse signaling pathways. Due to its complex pathogenesis and diverse clinical manifestations, there are challenges in the diagnosis and treatment in clinic. This paper aims to provide a comprehensive review on recent advances in understanding the immunological pathogenesis of alopecia areata by focusing on mechanisms underlying immune privilege loss around hair follicles and the interaction between various immune cells in the microenvironment for a deeper understanding of its pathogenesis. It also seeks to explore new research directions and potential treatment strategies.